Earthworms (Clitellata, Megadrili) of the world: an updated checklist of valid species and families, with notes on their distribution - Misirlioğlu, Mete; Reynolds, John Warren; Stojanović, Mirjana; Trakić, Tanja; Sekulić, Jovana; James, Samuel W.; Csuzdi, Csaba; Decaëns, Thibaud; Lapied, Emmanuel; Phillips, Helen R. P.; Cameron, Erin K.; Brown, George G. (Zootaxa, 2023)
In the current paper we present an updated checklist of all the megadrile earthworms (Crassiclitellata: Annelida) in the world, and notes on the distribution of families worldwide. Biogeographic responses to geological phenomena including plate tectonics, as well as to past and present climate and habitat distributions, are the main factors determining the present distribution of earthworm families. A total of ca. 5,738 species/subspecies (5,406 species and 332 unique subspecies; i.e., not counting the nomino-typical subspecies) belonging to 23 families (including one non-crassiclitellate family: Moniligastridae) are currently recognized worldwide, of which three families (Tritogeniidae and Kazimierzidae from Southern Africa and Arecoidae, a new family from Brazil described herein), 35 genera and close to 1200 new taxa (including subspecies) were described in the 21st century. Nonetheless, the large number of still undescribed species will likely increase this value to well over 8,000 species. Ten families are monospecific and/or monogeneric and have a mostly restricted distribution. On the other hand, more than 87 widespread cosmopolitan species have been catalogued, some of them with important invasive potential, belonging mainly to families Lumbricidae, Acanthodrilidae, Benhamiidae, Megascolecidae, Rhinodrilidae and Ocnerodrilidae. Taxonomic housekeeping was performed for the preoccupied Rhinodrilidae genus Tairona Righi – herein substituted by Taironina nom. nov., and Guarani camaqua Rodríguez & Lima was reinstated and removed from synonymy with Criodrilus lacuum Hoffmeister, 1845, resulting in a wider definition of the Almidae family. Furthermore, Amynthas maximalis nom. nov. is proposed herein as a substitution name for the preoccupied name Amynthas maximus Qiu & Dong, 2019, and Arecoidae is proposed herein as a new monotypic family for the aquamegadrile species Areco reco Righi, Ayres & Bittencourt, 1978.